Effect of age on basal muscle protein synthesis and mTORC1 signaling in a large cohort of young and older men and women - Markofski, Melissa M.; Dickinson, Jared M.; Drummond, Micah J.; Fry, Christopher S.; Fujita, Satoshi; Gundermann, David M.; Glynn, Erin L.; Jennings, Kristofer; Paddon-Jones, Douglas; Reidy, Paul T.; Sheffield-Moore, Melinda; Timmerman, Kyle L.; et al. (Experimental gerontology, 2015)
The rate of muscle loss with aging is higher in men than women. However, women have smaller muscles throughout the adult life. Protein content is a major determinant of skeletal muscle size. This study was designed to determine if age and sex differentially impact basal muscle protein synthesis and mammalian/mechanistic target of rapamycin complex 1 (mTORC1) signaling. We performed a secondary data analysis on a cohort of 215 healthy, non-obese (BMI<30kg·m−2) young (18–40y; 74 men, 52 women) and older (60–87y; 57 men, 32 women) adults. The database contained information on physical characteristics, basal muscle protein fractional synthetic rate (FSR; n=215; stable isotope methodology) and mTORC1 signaling (n=125, Western blotting). FSR and mTORC1 signaling were measured at rest and after an overnight fast. mTORC1 and S6K1 phosphorylation were higher (p<0.05) in older subjects with no sex differences. However, there were no age or sex differences or interaction for muscle FSR (p>0.05). Body mass index, fat free mass, or body fat was not a significant covariate and did not influence the results. We conclude that age and sex do not influence basal muscle protein synthesis. However, basal mTORC1 hyperphosphorylation in the elderly may contribute to insulin resistance and the age-related anabolic resistance of skeletal muscle protein metabolism to nutrition and exercise. •The effect of age and sex on basal FSR from 215 participants was examined.•No sex or age differences in basal FSR were found, despite larger muscle mass in young men.•Body composition measures were not significant covariates.•Basal muscle mTOR phosphorylation was higher in older adults as compared to younger subjects.